Neglected perspectives on science and religion: historical and contemporary relations - Viney, Wayne (Routledge, 2017)
Intellectual warfare: arguments pro and con -- The problem of knowledge -- The problem of causality -- Causality continued: angels and demons -- Soul and body -- Evolution -- Galileo and the church -- Advances in understanding of the origins of sex -- Women and men: scientific and religious perspectives -- Sexual orientation: from harmony to discord to diaspora -- Religion and social metrics -- Absolutism: the disease of philosophical thought